Requirements For Effective Risk Management In Syrian Banking Sector - حليبيه, كنده (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The study aims to estimate the requirements of risk management procedures effectiveness in Syrian banking sector, and exams the existence of these requirements by detecting six factors as the requirements of risk management effectiveness according to the literature. The study used the survey method, the data was collected using a questionnaire developed according to literature review. Fifty questionnaires were send to the employees who work in risk management department in Syrian banks, but only thirty three were received back as an acceptable responses. The data was analyzed using SPSS. This paper showed that the requirements of risk management procedures effectiveness are available in some factors (support from top management, Communication, Information technology ) in banks, and they are not available in others factors( Culture, Organization structure, Training).